Identifying Limiting Processes in the Composite Cathode of All-Solid-State-Batteries by Structure-Resolved Simulations - Clausnitzer, Moritz; Hein, Simon; Mücke, Robert; Finsterbusch, Martin; Danner, Timo; Latz, Arnulf (2023)
All-solid-state batteries (ASSBs) are a promising technology for applications that demand high energy and power density. The utilization of solid electrolytes (SE) potentially enables the use of Li-metal anodes, theoretically providing a significant increase in energy density. However, practical values still fall short due to inadequate electrode design and degradation mechanisms. This is especially important for the composite cathode, which consists of a 3D-network of SE and cathode active material (CAM) particles. Cell performance is significantly influenced by the transport processes in the composite cathode that depend on its geometrical properties including CAM fraction, density and particle sizes. Additionally, interfacial stability issues between SE and CAM can lead to degradation phenomena during the manufacturing process and cycling of the cells [1,2]. Potentially, secondary phases can form a resistive layer and impede charge transfer at the interface. The additional charge transfer resistance is one explanation for the low measured cell capacity of garnet-based cells at room temperature [3]. In this contribution, we use structure-resolved simulations in the simulation framework BEST [4] to identify limitations of the cell performance. We focus on the optimization of the microstructure and correlate cell performance to geometrical properties of the composite cathode. This allows us to identify target values for the cell production regarding CAM fraction, sinter density as well as SE and CAM particle size. Additionally, we investigate the effect of secondary phases at the SE/CAM interface. In doing so, we can determine the influence on cell performance depending on the properties of the degradation products and provide possible explanations for the reduction in performance observed experimentally. References [1] Ihrig, M., Finsterbusch, M., Laptev, A. M., Tu, C. H., Tran, N. T. T., Lin, C. A., . & Guillon, O. (2022). Study of LiCoO2/Li7La3Zr2O12: Ta interface degradation in all-solid-state lithium ...